2023
DOI: 10.1182/blood.2022018956
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of platelet-inspired hemostatic nanoparticles on bleeding in Von Willebrand disease murine models

Abstract: The lack of innovation in Von Willebrand disease (VWD) originates from many factors including the complexity and heterogeneity of the disease but also from a lack of recognition of the impact of the bleeding symptoms experienced by VWD patients. Recently, a few research initiatives aiming to move past replacement therapies using plasma-derived or recombinant Von Willebrand factor (VWF) concentrates have started to emerge. Here we report an original approach using synthetic platelet (SP) nanoparticles for treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Furthermore, after separating tumor tissue from the liver, the tumor tissues from the PmMN@DiD group and the PmMN@DiD & magnetic field group exhibited stronger fluorescent signals compared to free DiD and MN@DiD (Figure C, E), which suggested that the Pm coating facilitated effective targeting and prolonged retention of nanoplatforms within HCC. It is well-known that HCC tissue contains an abundance of collagen, , and collagen can serve as an agent for platelet aggregation. , We hypothesized that the PmMN@Om&As might target and adhere to HCC tissue through the recognition of Pm coating to collagen. We substantiated this hypothesis through a simulated blood perfusion experiment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, after separating tumor tissue from the liver, the tumor tissues from the PmMN@DiD group and the PmMN@DiD & magnetic field group exhibited stronger fluorescent signals compared to free DiD and MN@DiD (Figure C, E), which suggested that the Pm coating facilitated effective targeting and prolonged retention of nanoplatforms within HCC. It is well-known that HCC tissue contains an abundance of collagen, , and collagen can serve as an agent for platelet aggregation. , We hypothesized that the PmMN@Om&As might target and adhere to HCC tissue through the recognition of Pm coating to collagen. We substantiated this hypothesis through a simulated blood perfusion experiment.…”
Section: Resultsmentioning
confidence: 99%
“…It is well-known that HCC tissue contains an abundance of collagen, 63,64 and collagen can serve as an agent for platelet aggregation. 65,66 We hypothesized that the PmMN@Om&As might target and adhere to HCC tissue through the recognition of Pm coating to collagen. We substantiated this hypothesis through a simulated blood perfusion experiment.…”
Section: Inhibition Of Caf Activity and Enhancement Of Til Mitochondr...mentioning
confidence: 99%
“…In type 2B VWD, recent advances have moved away from replacement therapies to investigating synthetic nanoparticles. 88 Those nanoparticles are able to concomitantly bind to VWF, collagen, and activated platelets, and therefore improve thrombus formation in vitro. Moreover, they reduced blood loss in type 2B VWD mice by 35% and in a type 3 VWD model (i.e., VWF knockout mice) by 68% with a strong clot similar to wild type mice.…”
Section: Nanobody Cross-linking Vwf With Albumin In Quantitative Von ...mentioning
confidence: 99%
“…Moreover, they reduced blood loss in type 2B VWD mice by 35% and in a type 3 VWD model (i.e., VWF knockout mice) by 68% with a strong clot similar to wild type mice. 88 These results and the fact that those synthetic nanoparticles have a long half-life make them a possible treatment option to be tested in future clinical trials. 88…”
Section: Nanobody Cross-linking Vwf With Albumin In Quantitative Von ...mentioning
confidence: 99%
See 1 more Smart Citation